Pengaruh Kompensasi Finansial Dan Non Finansial Terhadap Kinerja Pengurus Dan Pegawai Bumdesma Se Kabupaten Tanah Datar Yang Di Mediasi Motivasi Kerja - Zulli Rustam; Anne Putri; Imran Imran (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Compensation is one of the key factors in human resource management, as it can influence the level of employee motivation and performance. This study aims to analyze the effect of financial and non-financial compensation on the performance of managers and employees of BUMDESMA in Tanah Datar Regency, with work motivation as a mediating variable. The object of this study includes all managers and employees of BUMDESMA (Joint Village-Owned Enterprises) in Tanah Datar Regency, totaling 60 individuals, who were also used as the research sample. This study employs the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). The results indicate that financial compensation has a negative and significant effect on the performance of managers and employees of BUMDESMA. Meanwhile, non-financial compensation has a positive and significant effect on performance. Work motivation is also found to have a positive and significant effect on the performance of managers and employees. In addition, both financial and non-financial compensation have a positive and significant effect on work motivation. The findings further reveal that work motivation is able to mediate the effect of both financial and non-financial compensation on the performance of managers and employees of BUMDESMA in Tanah Datar Regency.